Synthesis of Fe-substituted aluminosilicate and aluminogermanate nanotubes - Bac, Bui Hoang; Song, Yungoo (VNU Journal of Science: Mathematics - Physics; Vol 27 No 4, 2011)
Abstract: In this paper, substitution of Fe 3+ for Al 3+ in the structure of aluminosilicate and aluminogermanate nanotubes was investigated at various mole ratios of Fe/Al from the mixed Al 2 O 3 -Fe 2 O 3 -SiO 2 (GeO 2 )-H 2 O solution in experimental conditions of 2 mM initial concentration and 2 day aging time at 98 0 C. The synthesized products were confirmed and characterized by using FT-IR spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM) and magnetometer. The results indicated that Fe-substituted aluminosilicate and aluminogermanate nanotubes were successfully synthesized with the Fe/Al ratio of the initial solutions up to 2. For both Fe-substituted nanotubes, the paramagnetic property exhibits at room temperature (300 K) and a ferromagnetic property at low temperature (5 K). The materials with new properties appear to have promising practical application in other fields in the future. Key words: Imogolite, nanotube, substitution, aluminosilicate, aluminogermanate